Gift Cards Fraud: Challenges and Strategies for Consumer Protection in the Digital Age - Prayuti, Yuyut (Law Development Journal, 2023)
The prepaid card industry in Indonesia, particularly gift cards, has exhibited significant growth in recent years. In 2023, the industry is projected to grow by 10.6% annually, reaching an estimated value of approximately US$1,958.4 million. The Indonesian gift card market recorded a Compound Annual Growth Rate (CAGR) of 11.4% from 2018 to 2022. The susceptibility of gift cards to fraud is a significant concern due to several intrinsic characteristics. This study aims to identify the various challenges in gift card payment fraud and analyze preventative strategies that could prove effective in addressing this issue. The research method used is normative juridical with a statute approach, case approach, analytical approach, and comparative approach. The conclusion of this paper emphasizes the importance of a holistic approach to addressing payment fraud using gift cards. The significant growth of the gift card industry in Indonesia must be accompanied by improved security and consumer education. This comprehensive approach is expected to close the loopholes exploited by fraudsters and result in effective consumer protection.